SSRC:source rate control algorithm for delay-sensitive flow in data center network - Yang YANG; Min CAO; Jiahai YANG; Rong CHE; Wei LIU (Tongxin xuebao)
Previous work had studied how to ensure the transmission time of delay-sensitive flows,but falled short in its effectiveness for a given period.Motivated by that and based on SDN/OpenFlow framework,a SDN-based source rate control (SSRC) algorithm was proposed.With a global view of network,SSRC can quickly locate the potential congestion node,adjust the transmission rate of source and reduce the response time of SSRC.The experiment results show that compared with DCTCP and other algorithms,SSRC can shorten the completion time of flows by 75% in average,which can ensure the transmission time of delay-sensitive and solve the problem of Incast well.